Cover Image. Issue 11 (1st July 2021) - Buimer, Elizabeth E. L.; Schnack, Hugo G.; Caspi, Yaron; van Haren, Neeltje E. M.; Milchenko, Mikhail; Pas, Pascal; ,; Hulshoff Pol, Hilleke E.; Brouwer, Rachel M.
Abstract : COVER ILLUSTRATION Anatomical MRI brain scans contain facial characteristics. De‐identification methods remove or blur these facial characteristics. However, we show that de‐identification methods have a small effect on FreeSurfer brain measures. Furthermore, some methods are too invasive in younger participants or do not always succeed to remove all facial characteristics. The 3D‐rendered MRI scan on the cover is an average brain scan and therefore does not contain identifiable characteristics.